Business in the Base of the Pyramid: A Literature Review and Directions for Future Research - López-Morales, José Satsumi; Rosario-Flores, Felipe de Jesús; Huerta-Estevez, Antonio (Organizations and Markets in Emerging Economies, 2020)
The base of the pyramid (BoP) is the lower-income segment of the population. It represents an important market that is often disregarded by companies as a source of economic benefit. For this reason, scholars have gained interest in this topic since the early 21st century. The main objective of this article is to identify research areas related to business in the BoP. A qualitative investigation was carried out by reviewing the business literature on the BoP. Sixty-seven articles related to the topic were reviewed. This literature review was conducted using the four-stage qualitative method, including : (1) data collection; (2) data coding; (3) data analysis; and (4) interpretation of results. The result of the review was the identification of 12 gaps that must be addressed to improve the understanding of the BoP businesses. A description of the articles selected for the review is presented.
Keywords: Base of the pyramid; Bottom of the pyramid; Literature Review; Poverty Alleviation